Use of magnetic port finder for metallic foreign body extraction in hand - Guevara Valmaña, Osvaldo I.; Triguieros-Guzman, Sebastian; Fattel-Servin, Omar S.; Prieto-Vargas, Valentina; Balderas-Ruiz, Katia; Apellaniz-campo, Armando; Tellez-Placios, Daniela (International Journal of Research in Medical Sciences, 2023)
Foreign bodies are defined as any foreign object that enters the human body due to various circumstances. FBs are a common reason for emergency department visits. The hand’s complex vascular and nervous structures make aggressive exploration dangerous. FBs can be composed of various materials, making their detection with a single imaging study difficult. We propose using a magnetic tissue expander locator for intraoperative FB localization, presenting the case of a 50-year-old female patient who, after falling from her height, presented with a foreign body in her right hand. Due to the complexity of locating the FB, we used the magnetic finder, successfully extracting it without damaging any underlying structures. Use of magnetic tissue expander locators are effective, practical, and safe alternative to help for locating magnetic foreign bodies.